EDUKASI DAN PELATIHAN KELOMPOK MASYARAKAT TENTANG BANK SAMPAH - prayogi, bisepta; Risa Mariana, Evi; Pahruddin, Muhammad (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2023)
ABSTRACT Waste has always been a difficult problem for people who don't care about the environment. When people don't keep things clean, they can leave behind unpleasant piles of trash. According to the World Bank report "What a Waste: A Global Review of Solid Waste Management", the amount of solid waste in cities around the world will increase by 70% from this year to 2025, increasing from 1.3 billion tons per year to 2.2 billion tons per year. This community service activity aims to change how people dispose of rubbish on the banks of the river in the Astambul Community Health Center Working Area, Banjar Regency and increase residents' income in Jati Baru Village. At the implementation stage, the community service team will start activities by providing training and counselling about waste management and waste banks to community groups. At the evaluation stage, the community service team will assess the level of residents' knowledge about waste management and processing. They will also monitor the waste bank that has been formed. The results of this community service activity include that the level of knowledge of the Jati village community has increased after being educated about managing waste. There were 23 people (76.7%) who had a good level of knowledge, of the formation of a waste bank in Jati Baru village, and the establishment of cooperation between the Jati Baru village waste bank and Sekumpul waste bank for waste management. This community service activity can increase the knowledge of the Jati Baru village community about good waste management. This community service activity provides an alternative solution to handling the waste problem in Jati Baru village by forming a waste bank. This community service activity is a means of transferring technology from educational institutions to the community in the form of educational modules about waste management through waste banks. Keyword: Waste Management, Environmental Health, Waste Bank, Community Service